Electrochemical machining of molybdenum. (December 2021) - Schneider, M.; Šimůnková, L.; Michaelis, A.; Hoogsteen, W.
Abstract: The present work focuses on the anodic dissolution mechanism of molybdenum and the quantification of oxygen evolution as a possible side reaction. Molybdenum dissolution was studied in sodium nitrate solution under acidic (pH 1) and alkaline (pH 12) conditions at high current densities, which is typical for the industrial electrochemical machining process (ECM). The anodic oxygen evolution was evidenced by using the fluorescence quenching technique. The oxygen efficiency amounts to ≈1% at pH 12 and ≈7% at pH 1. These and considering previous results, lead to the assumption that a part of molybdenum does not dissolve as Mo 6+ . This agrees with oxidation of dissolved ions in a subsequently coupled amperometric cell at pH 12. The evolution of oxygen as well as supplementary material diagnostics clearly shows the (trans-)passive dissolution of molybdenum via the formation and dissolution of molybdenum oxide films under acidic as well as under alkaline conditions in sodium nitrate solutions. Considering all data, the authors conclude that the average valency is slightly lower than z = 5.5 at pH 1 and z = 5.9 at pH 12. The assumption of the partial dissolution of lower valent molybdenum ions is supported by the observation of a blue coloring of the remaining electrolyte on the sample surface after the experiments. Highlights: Molybdenum anodically dissolves via passive state under alkaline as well as acidic conditions. The dissolution takes place with an average valency of z ≈ 5.5 (at pH 1) and z ≈ 5.9 (at pH 12). Oxygen evolution as side reaction was quantitatively evidenced.